2014
DOI: 10.1088/0953-8984/26/35/355801
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of amorphous/crystalline silicon superlattices

Abstract: Thermal transport properties of crystalline/amorphous silicon superlattices using molecular dynamics are investigated. We show that the cross-plane conductivity of the superlattices is very low and close to the conductivity of bulk amorphous silicon even for amorphous layers as thin as ≃ 6 Å. The cross-plane thermal conductivity weakly increases with temperature which is associated with a decrease of the Kapitza resistance with temperature at the crystalline/amorphous interface. This property is further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 43 publications
4
58
1
Order By: Relevance
“…Typically, structural disorders have been observed only by atomic visualization. 13,14,39,48,49 Therefore, using correct bins is necessary to provide insight into the interface characteristics.…”
Section: The Proper Bin Size For Correct Measurements At Grain Bmentioning
confidence: 99%
“…Typically, structural disorders have been observed only by atomic visualization. 13,14,39,48,49 Therefore, using correct bins is necessary to provide insight into the interface characteristics.…”
Section: The Proper Bin Size For Correct Measurements At Grain Bmentioning
confidence: 99%
“…In Ref. [216] similar results are obtained for a-Si/mass-heavy c-Si SLs where they show a very slight increase in thermal conductivity with temperature.…”
Section: Sensitivity To Ratiosupporting
confidence: 71%
“…Thus, we compute the thermal conductivity of an infinite size system with spherical nano-pores periodically spread across the material. A shell of amorphous Silicon can be added around the pore with a "cut and paste technique" [6,7,8] . The thickness of the shell can also vary.…”
Section: Modeling the Structuresmentioning
confidence: 99%
“…It has been shown that phonons feel the existence of the crystalline/amorphous interface in a distance of almost 1 nm from the interface [6].…”
Section: Effect Of the Amorphous Shellmentioning
confidence: 99%